Zn and Zn-Fe nanostructures with multifunctional properties as components for food packaging materials - Lamsaf, Hafsae (2022)
Metallic and bimetallic nanostructures have shown interesting chromatic and antibacterial properties, and they can be used in various applications. In this work, zinc (Zn) and iron (Fe) nanostructures were produced with different morphologies: (i) pure Zn; (ii) Zn-Fe nanoalloys; (iii) Zn-Fe nanolayers (Zn-Fe NLs); and (iv) Zn nanolayers combined with Fe nanoparticles (Zn NLs + Fe NPs). The aim was to produce components for food packaging materials with active and intelligent properties, including oxygen absorption capacity, chromatic properties, and antibacterial properties. Thus, the morphology, structure, and chemical composition of the samples were characterized and correlated with their oxidation, chromatic, and antibacterial properties. The results revealed a relevant reduction in the coating’s opacity after oxidation varying from 100 to 10% depending on the morphology of the system. All coatings exhibited significant antibacterial activity against S. aureus, revealing a direct correlation with Zn content. The incorporation of Fe for all atomic arrangements showed a negative impact on the antibacterial effect against E. coli, decreasing to less than half the zone of inhibition for Zn-Fe NLs and Zn NLs + Fe NPs and suppressing the antibacterial effect for Zn-Fe alloy when compared with the pure Zn system.